Parental support, savings and student loan repayment - Lance Lochner; Todd R. Stinebrickner; Utku Suleymanoglu (The University of Western Ontario, Centre for Human Capital and Productivity (CHCP), 2018)
Using unique survey and administrative data from the Canada Student Loans Program, we document that parental support and personal savings substantially lower student loan repayment problems. We develop a theoretical model for studying student borrowing and repayment in the presence of risky labor market outcomes, moral hazard, and costly earnings verification. This framework demonstrates that non-monetary costs of applying for income-based repayment assistance are critical to understanding why resources other than earnings lead to greater repayment. We further show that eliminating these non-monetary costs may be inefficient and lead to undesirable redistribution. Empirically, we demonstrate that expanding Canada's income-based Repayment Assistance Plan to automatically cover all borrowers would likely reduce program revenue by nearly one-half over early years of repayment. Finally, we show how student loan programs can be more efficiently designed to address heterogeneity in parental transfers in the presence of non-monetary earnings verification costs and moral hazard.
Keywords: 330